Detection of Rickettsia lusitaniae Among Ornithodoros sawaii Soft Ticks Collected From Japanese Murrelet Seabird Nest Material From Gugul Island, Republic of Korea. Issue 3 (22nd February 2021) - Kim, Heung-Chul; Jiang, Ju; Hang, Jun; Kim, Su Yeon; Yun, Seok-Min; Park, Chang-uk; Kim, Miran; Chong, Sung-Tae; Farris, Christina M; Richards, Allen L; Klein, Terry A
Abstract: In a follow-up to the investigations of soft ticks identified from seabird nest soil and litter collected from coastal islands of the Republic of Korea (ROK), Ornithodoros sawaii and Ornithodoros capensis were assessed for the presence and identification of rickettsiae. Ticks collected from samples of 50–100 g of nest litter and soil from seabird nests were identified individually by morphological techniques, and species confirmed by sequencing of the mt- rrs gene. Subsequently, tick DNA preparations were screened for the presence of rickettsiae using a genus-specific nested PCR (nPCR) assay targeting the 17 kDa antigen gene. The amplicons from the 17 kDa assay and two additional nPCR assays targeting the gltA and ompB gene fragments were sequenced and used to identify the rickettsiae. A total of 134 soft ticks belonging to two species, O. sawaii Kitaoka & Suzuki 1973 ( n = 125) and O. capensis Neumann 1901 ( n = 9), were collected. Rickettsia lusitaniae DNA was detected and identified among O. sawaii ticks ( n = 11, 8.8%) collected from nest litter and soil of the Japanese murrelet ( Synthliboramphus wumizusume Temminck 1836) at Gugul Island along the western coastal area of the ROK. This study confirmed for the first time the presence of R. lusitaniae associated with O. sawaii collected from migratory seabird nests in the ROK.